Enhancing Knowledge Management Quality in School through the SECI Model - Ahmad Yahya Alchilma; Nahdhiana, Izzah Zulfa; Shabrina, Nabila Nur; Permadi, Danur Putut (JENTRE, 2024)
Education plays a crucial role in shaping the personality and character of students. Knowledge management is a key component in education aimed at enhancing human resource quality. However, implementing knowledge management can be challenging in Indonesia. This study aims to analyze the knowledge management system at SMP Muhammadiyah 1 Surakarta using the SECI model (Socialization, Externalization, Combination, and Internalization). This research adopts a qualitative approach with a field study methodology. Data were collected through documentation, interviews, and observations involving the principal, educators, vice principals, teachers, students, and the school's social media platforms such as Instagram, TikTok, and YouTube. To ensure data validity, qualitative descriptive analysis was applied. The findings indicate that SMP Muhammadiyah 1 Surakarta has implemented a knowledge management system within its curriculum, but it is not yet fully effective. The school employs two curricula: the Merdeka Curriculum and the K13 Curriculum, each tailored to the needs of the students. Key challenges include human resources, infrastructure, budget, and technology. Through the application of the SECI model, knowledge management has proven to be beneficial in generating new knowledge and improving the quality of education in the institution. This study concludes that optimizing knowledge management using the SECI model can enhance both the quality of education and the overall knowledge management system at SMP Muhammadiyah 1 Surakarta. This is achieved through the principal’s delegation of tasks and the provision of training to educators, aimed at enhancing their technological skills and teaching methodologies.